O Sumo Bem e a moralidade em Kant: a função do conceito de Sumo Bem no processo de desenvolvimento da filosofia crítica - Cortes, Rafael da Silva (2010)
This master thesis aims at reconstructing the Kantian concept of the Highest Good (höchstes Gut) since its presentation in the Critique of pure reason`s Transcendental doctrine of method (1781), passing by Groundwork of the metaphysic of morals (1785) and the Critique of practical reason (1788), until the preface of The religion within the limits of reason alone (1793). We intend here to clarify the definition that Kant presents about the concept of the Highest Good, as well as its relation with morality. That way, we maintain that in the development of the critical philosophy Kant presented different perspectives about the Highest Good, taking into account the different meanings this concept has in Kant. The same applies to Kant s conception of the foundations of moral, considering that his arguments in different stages of the critical philosophy sometimes are unstable about the determination of the origin of the moral law. Thus, it is necessary to analyze the relation of morality to the Highest Good, because it is an extremely important element of this concept. After clarifying this relation, we approach the question, linked to Highest Good and morality, about how happiness can be an element of the concept of such object without compromising its characteristic of originating from pure rational will. Furthermore, we approached the problem of the importance of the Highest Good for Kant`s practical philosophy. We take the doctrine of the practical reason`s postulates as relevant to this question. Finally, we go into Kant`s philosophy of religion in which the concept of the Highest Good seems to adopt an anthropological character, representing the final end that rational human beings aim to attain.